The Eucalyptus grandis NBS-LRR gene family: physical clustering and expression hotspots - Nanette eChristie; Peri Ann Tobias; Sanushka eNaidoo; Carsten eKülheim (Frontiers in Plant Science, 2016)
Eucalyptus grandis is a commercially important hardwood species and is known to be susceptible to a number of pests and pathogens. Determining mechanisms of defense is therefore a research priority. The published genome for E. grandis has aided the identification of one important class of resistance (R) genes that incorporate nucleotide binding sites and leucine-rich repeat domains (NBS-LRR). Using an iterative search process we identified NBS-LRR gene models within the E. grandis genome. We characterized the gene models and identified their genomic arrangement. The gene expression patterns were examined in E. grandis clones, challenged with a fungal pathogen (Chrysoporthe austroafricana) and insect pest (Leptocybe invasa). 1215 putative NBS-LRR coding sequences were located which aligned into two large classes, Toll or interleukin-1 receptor (TIR) and coiled-coil (CC) based on NB-ARC domains. NBS-LRR gene-rich regions were identified with 76% organized in clusters of three or more genes. A further 272 putative incomplete resistance genes were also identified. We determined that E. grandis has a higher ratio of TIR to CC classed genes compared to other woody plant species as well as a smaller percentage of single NBS-LRR genes. Transcriptome profiles indicated expression hotspots, within physical clusters, including expression of many incomplete genes. The clustering of putative NBS-LRR genes correlates with differential expression responses in resistant and susceptible plants indicating functional relevance for the physical arrangement of this gene family. This analysis of the repertoire and expression of E. grandis putative NBS-LRR genes provides an important resource for the identification of novel and functional R-genes; a key objective for strategies to enhance resilience.